PERCEIVED RISK AND ITS ROLE IN THE INFLUENCE OF BRAND AWARENESS ON PURCHASE INTENTION: A STUDY OF TRAVELOKA USERS - Diva Dara Islami; Faizal Hamzah (RADJA PUBLIKA, 2026)
This study examines the role of perceived risk in the influence of brand awareness on purchase intention among Traveloka users. The rapid growth of Online Travel Agencies (OTAs) has changed consumer behavior in searching, comparing, and purchasing travel services through digital platforms. Although Traveloka has strong brand awareness in Indonesia, consumers may still experience uncertainty related to online transactions, such as payment security, privacy protection, refund delays, and service mismatches. This study uses a quantitative approach with a survey method. Data are collected through an online questionnaire distributed to respondents who have used the Traveloka application and have experience searching for or purchasing travel-related services. The data analysis includes validity testing, reliability testing, linear regression analysis, and mediation testing. The findings indicate that brand awareness can encourage purchase intention by increasing consumer familiarity and confidence. However, perceived risk plays an important role in weakening or explaining this relationship. When perceived risk is high, consumers’ intention to purchase through Traveloka may decrease, even though they recognize the brand. Therefore, Traveloka needs to strengthen brand awareness while reducing perceived risk through secure transactions, transparent information, reliable services, and responsive customer support.